Microstructural and shear strength properties of GNSs-reinforced Sn-1.0Ag-0.5Cu (SAC105) composite solder interconnects on plain Cu and ENIAg surface finish - K., Vidyatharran; M. A., Azmah Hanim; Dele-Afolabi, T. T.; Matori, K. A.; O., Saliza Azlina (Elsevier, 2021)
In this study, the combined effect of GNSs (graphene nanosheets) and ENIAg (Electroless Nickel Immersion Silver) surface finish on the formation of intermetallic compounds (IMCs) and shear strength of the Sn-1.0Ag-0.5Cu (SAC105) solder system was studied. Both plain and composite solder systems (SAC105-xGNS; x = 0, 0.01, 0.05 and 0.1 wt%) were successfully prepared using the powder metallurgy technique and thereafter soldered on the plain Cu and ENIAg surface finish substrates. From the microstructural analysis, the Cu6Sn5 IMC was observed at the solder/substrate interface of the SAC105-xGNS/Cu solder joints. Moreover, the Ni3Sn4 and (Cu,Ni)6Sn5 IMC phases were observed at the solder/substrate interface of the SAC105-xGNS/ENIAg counterparts. The GNSs and ENIAg surface finish provided huge barrier for Sn and Cu atoms diffusion required for IMC formation. The interfacial IMC layer thickness decreased with increasing addition of GNSs for both sample grades. The SAC105-xGNS/ENIAg demonstrated lower IMC thicknesses that ranged between 2.98 and 2.53 μm relative to the 5.23–3.35 μm exhibited by the SAC105-xGNS/Cu. In general, the strengthening potential of the GNSs was well marked in both sample grades, with the SAC105-0.01GNS/Cu and SAC105-0.01GNS/ENIAg demonstrating the highest shear strengths of 11.2 MPa and 12.1 MPa, respectively.